FENOMENA POLITIK SOROH TERHADAP SIKAP POLITIK ORGANISASI MGPSSR DALAM PILKADA SERENTAK KABUPATEN KARANGASEM TAHUN 2015 - Saraswati, Dwi Ratih; Erviantono, Tedi; Noak, Piers Andreas (Jurnal Nawala Politika, 2016)
ABSTRACT This paper aims to see how such a family-based organization MGPSSR (Maha Gotra Pasek Sanak Sapta Rsi) determine political attitudes in the elections of 2015. Simultaneously Karangasem Soroh seen as social ties within the community people Hindus in Bali which refers to one lineage (dynasty) the same one. This potential was realized by interest groups as one of the factors for support. The emotional response of citizens Pasek (MGPSSR) start flowing on candidates who have a common background of the offspring.Depart by using the theory of dramaturgy and qualitative research methods-descriptive. Research conducted in Karangasem regency showed that the formation of the Volunteer 157 as a continuation MGPSSR to engage in politics and support the candidate of his choice. This study found the implication that soroh can be a major factor supporting the victory of candidates who have the same background as well as to be the main factor causing the impartiatyof victory itself. Keywords: Political Soroh, MGPSSR (Maha Gotra Pasek Sanak Sapta Rsi), elections, Karangasem